Monitoring and Reporting Of Quality in Statistics - Lukšaitė-Balakauskienė, Laura (Lithuanian Journal of Statistics, 2018)
[full article, abstract in English; abstract in Lithuanian] The present paper introduces the main principles of the quality management system of Statistics Lithuania, which is based on the ISO 9001 standard, and explains how the system promotes user confidence in statistics through the regular quality monitoring and reporting exercise. It is explained how the quality of statistics is measured and presented to the public; the usefulness of quality reports to the users, especially to researchers and academia, is discussed. Moreover, some results from the monitoring exercise and examples of quality reports are presented.